Determination of native lactoferrin and other whey proteins at different pH conditions after UHT using reverse phase HPLC. (June 2023) - Williams, A.M.; Zhou, Y.; Luo, N.; Hoekstra, T.M.; Oh, H.E.; Bennison, C.
Abstract: Whey proteins such as lactoferrin are high value components in milk; however, under UHT conditions they can denature and lose their functionality and bioactivity. The heat stability of these proteins in water suspensions was investigated at different pH conditions using a pilot scale UHT plant. An RP-HPLC method was used to quantify β-lactoglobulin, α-lactalbumin and lactoferrin simultaneously. In a pH 3.0–5.0 lactoferrin-in-water suspension, at least 48% of undenatured lactoferrin remained after UHT. The highest level of undenatured lactoferrin was 81%, observed at pH 4.0; the iron binding capacity for this sample was 78%. In addition, mixtures of whey protein concentrate and lactoferrin in a lactose solution were investigated, which showed 84% and 70% nativity for whey at pH 3.0 and pH 3.5, respectively, and 78% nativity for lactoferrin at pH 3.5. These results provide useful information in product research and development to maintain bioactive protein nativity through UHT processing.